2022
DOI: 10.3389/fphar.2022.965694
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a traditional Chinese quadri-combination therapy and its component quercetin on recurrent spontaneous abortion: A clinical trial, network pharmacology and experiments-based study

Abstract: Objective: To explore the effect and mechanisms of a traditional Chinese quadri-combination therapy [Bushen, Yiqi, Lixue and Yangtai (BYLY)] in treating recurrent spontaneous abortion (RSA).Methods: A clinical trial was conducted to study the effect of BYLY on RSA. Pharmacological network analysis and UPLC-Q/TOF-mass spectrometry (MS) were applied to investigate the key active component in BYLY and potential targets. Cellular experiments based on former results were performed to examine the mechanism of BYLY i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Moreover, cao et al (59) found that quercetin counteracted hyperglycemia-induced nitrosative stress and oxidative stress, decreased the levels of oxidative stress markers and increased the expression of superoxide dismutase 1 and 2 and ultimately reduced the rate of embryonic malformations in diabetic pregnant mice. in addition, in vitro experiments have demonstrated that quercetin at appropriate concentrations can improve biological function, mitochondrial membrane potential and morphology of trophoblast cells under hypoxic conditions (60). decidual natural killer (nK) cells are the primary immune cell population at the maternal-fetal interface, with low cytotoxicity (61), which enhance decidual cell invasion as well as spiral artery remodeling through the secretion of matrix metalloproteinases, vascular endothelial growth factor and interleukins, regulating maternal-fetal immune tolerance and placental developmental capacity (62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cao et al (59) found that quercetin counteracted hyperglycemia-induced nitrosative stress and oxidative stress, decreased the levels of oxidative stress markers and increased the expression of superoxide dismutase 1 and 2 and ultimately reduced the rate of embryonic malformations in diabetic pregnant mice. in addition, in vitro experiments have demonstrated that quercetin at appropriate concentrations can improve biological function, mitochondrial membrane potential and morphology of trophoblast cells under hypoxic conditions (60). decidual natural killer (nK) cells are the primary immune cell population at the maternal-fetal interface, with low cytotoxicity (61), which enhance decidual cell invasion as well as spiral artery remodeling through the secretion of matrix metalloproteinases, vascular endothelial growth factor and interleukins, regulating maternal-fetal immune tolerance and placental developmental capacity (62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…The composition of TCM is complex; all kinds of Chinese medicine often have some similar chemical components, so the search for the main effective components will help to analyze the key points of Chinese medicine in treating diseases and provide direction for the follow-up molecular mechanism. Network pharmacology, a biological system analysis approach, was utilized to uncover the relationship between multi-component medicines and the network target of diseases (20)(21). The topological analysis found twenty key targets of KLP, including TP53, ESR1, EGFR, MAPK3, AKT1, TNF, STAT3, CTNNB1, IL6, HIF1A, MYC, FOS, PTGS2, MMP9, CCND1, IL1β, HSP90AA1, PTEN, CXCL8, and IL10.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, four hundred and eighty participants were assigned to the clinical trial, it was shown that combined duphaston and BYLY could decrease the rate of early abortion compared with the use of duphaston or BYLY alone. It is believed that a possible mechanism is the protective effect of quercetin on trophoblasts by decreasing Drp1 expression through regulating miR-34a-5p [112]. In another randomized, doubleblind, placebo-controlled trial using quercetin for two weeks, the results revealed that alanine aminotransferase (ALT), aspartate aminotransferase (AST), and gamma-glutamyl transferase (GGT) were decreased by 50.4%, 37.2%, and 89.9%, respectively.…”
Section: Other Therapeutic Effectsmentioning
confidence: 99%